Economic Recovary Model in the Time of Pandemic COVID 19 a Case Study in Lombok West Nusatenggara Indonesia - . Kholil; Nafiah Ariani (Current Topics in Agricultural Sciences Vol. 2, 2021)
Covid 19 pandemic has a very serious impact to all productive activities of the people especially in Lombok West Nusatenggara, because the people have not recovered from the earthquake on July 2018, they have to face the pandemic covid since march 2020. Trygona honey is a leading home industry in accordance with the natural and cultural potential of the community, but it has not been fully developed for the economic recovery of the community during the COVID-19 pandemic. The purpose of this research is to develop the most appropriate strategy of commercialization of trygona honey to ensure sustainabiloity in the time of covid 19 pandemic, that can be used as a model for economic recovery in Indonesia. The analytical methods used are SAST (Strategic Assumption Surfacing and Testing), and AHP (Analytical Hierarchy Process). The results of study showed that trygona honey home industry was not affected by pandemic covid 19, the demand is actually increasing due to people’s awareness of their health. This honey has a very complete nutritional content, which can be used to increase immunity against of COVID-19. There are three main problems that were faced by the trigona bee farmers to develop their business: Trigona seeds, cultivation technology, and business management. The best strategy to increase their business and income is cultivation system technology and providing added value through packaging and labeling. The most appropriate commercialization strategy to increase farmer’s income and ensuring sustainability of the business is involving BUMDES as an interconectivity institution between trygona honey producers with the market.